The future of biomass and bioenergy deployment and trade: a synthesis of 15 years IEA Bioenergy Task 40 on sustainable bioenergy trade. (12th March 2019) - Junginger, Hans Martin; Mai‐Moulin, Thuy; Daioglou, Vassilis; Fritsche, Uwe; Guisson, Ruben; Hennig, Christiane; Thrän, Daniela; Heinimö, Jussi; Hess, J Richard; Lamers, Patrick; Li, Chenlin; Kwant, Kees; et al.
Abstract: Current biomass production and trade volumes for energy and new materials and bio‐chemicals are only a small fraction to achieve the bioenergy levels suggested by many global energy and climate change mitigation scenarios for 2050. However, comprehensive sustainability of large scale biomass production and trading has yet to be secured, and governance of developing biomass markets is a critical issue. Fundamental choices need to be made on how to develop sustainable biomass supply chains and govern sustainable international biomass markets. The aim of this paper is to provide a vision of how widespread trade and deployment of biomass for energy purposes can be integrated with the wider (bio)economy. It provides an overview of past and current trade flows of the main bioenergy products, and discusses the most important drivers and barriers for bioenergy in general, and more specifically the further development of bioenergy trade over the coming years. It discusses the role of bioenergy as part of the bioeconomy and other potential roles; and how it can help to achieve the sustainable development goals. The paper concludes that it is critical to demonstrate innovative and integrated value chains for biofuels, bioproducts, and biopower that can respond with agility to market factors while providing economic, environmental, and societal benefits to international trade and market. Furthermore, flexible biogenic carbon supply nets based on broad feedstock portfolios and multiple energy and material utilization pathways will reduce risks for involved stakeholder and foster the market entry and uptake of various densified biogenic carbon carriers. © 2019 Society of Chemical Industry and John Wiley & Sons, Ltd